First Evidence of Acyl-Hydrolase/Lipase Activity From Human Probiotic Bacteria: Lactobacillus rhamnosus GG and Bifidobacterium longum NCC 2705 - Manasian, Panagiotis; Bustos, Atma-Sol; Pålsson, Björn; Håkansson, Andreas; Peñarrieta, J. Mauricio; Nilsson, Lars; Linares-Pastén, Javier A. (Frontiers in Microbiology, 2020)
Lactobacillus rhamnosus GG (ATCC 53103) and Bifidobacterium longum NCC 2705 are among the most studied probiotics. However, the first evidence of acyl hydrolase / lipase of two annotated proteins, one in each genome of these strains, is reported in this work. Signal peptide analysis has predicted that these proteins are exported to the extracellular medium. Both proteins were produced in Escherichia coli, purified and characterized. Molecular masses (without signal peptides) were 27 and 52.3 kDa for the proteins of L. rhamnosus and B. longum respectively. Asymmetrical flow field-flow fractionation analysis has shown that both proteins are present as monomers in their native forms at pH 7. Both have shown enzymatic activity on pNP-laurate at pH 7 and 37°C. The enzyme from L. rhamnosus was characterized deeper, showing preference on pNP-esters with short chain fatty acids. In addition, a computational model of the 3D structure has allowed the prediction of the catalytic amino acids. The enzymatic activities using synthetic substrates were very low for both enzymes. The investigation of natural substrates and biological functions of these enzymes is still open.